Soil metatranscriptomics for mining eukaryotic heavy metal resistance genes - Frédéric Lehembre; Didier Doillon; Elise David; Sandrine Perrotto; Jessica Baude; Julie Foulon; Lamia Harfouche; Laurent Vallon; Julie Poulain; Corinne Da Silva; Patrick Wincker; Christine Oger‐Desfeux; et al. (Environmental Microbiology, 2013)
Summary Heavy metals are pollutants which affect all organisms. Since a small number of eukaryotes have been investigated with respect to metal resistance, we hypothesize that many genes that control this phenomenon remain to be identified. This was tested by screening soil eukaryotic metatranscriptomes which encompass RNA from organisms belonging to the main eukaryotic phyla. Soil‐extracted polyadenylated mRNAs were converted into cDNAs and 35 of them were selected for their ability to rescue the metal ( Cd or Zn ) sensitive phenotype of yeast mutants. Few of the genes belonged to families known to confer metal resistance when overexpressed in yeast. Several of them were homologous to genes that had not been studied in the context of metal resistance. For instance, the BOLA ones, which conferred cross metal ( Zn , Co , Cd , Mn ) resistance may act by interfering with Fe homeostasis. Other genes, such as those encoding 110‐ to 130‐amino‐acid‐long, cysteine‐rich polypeptides, had no homologues in databases. This study confirms that functional metatranscriptomics represents a powerful approach to address basic biological processes in eukaryotes. The selected genes can be used to probe new pathways involved in metal homeostasis and to manipulate the resistance level of selected organisms.